Terapi Kelompok Terapeutik terhadap Identitas Diri Remaja - Sandra Cassia Amanda; Dewi Eka Putri; Feri Fernandes (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the effect of therapeutic group therapy on the self-identity of adolescents in Gunung Raya District, Kerinci Regency, in 2023. The method used is a quasi-experimental design with a pretest-posttest research design with a control group design. The study results showed a significant increase in adolescents' self-identity after therapeutic group therapy from moderately active to active self-identity status. The conclusion is that there are substantial differences in adolescents' self-identity after group activity therapy between the group that received therapeutic group therapy and the group that did not receive therapeutic group therapy. Keywords: Adolescent Self-Identity, Therapeutic Group Therapy